A Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) - rationale and design of a multicenter, randomized trial in depressed patients with CAD - Albus, Christian; Beutel, Manfred E.; Deter, Hans-Christian; Fritzsche, Kurt; Hellmich, Martin; Jordan, Jochen; Jünger, Jana; Krauth, Christian; Ladwig, Karl-Heinz; Michal, Matthias; Mueck-Weymann, Michael; Petrowski, Katja; et al. (Journal of psychosomatic research, 2011)
Objective - Depressive symptoms are highly relevant for the quality of life, health behavior, and prognosis in patients with coronary artery disease (CAD). However, previous psychotherapy trials in depressed CAD patients produced small to moderate effects on depression, and null effects on cardiac events. In this multicentre psychotherapy trial, symptoms of depression are treated together with the Type D pattern (negative affectivity and social inhibition) in a stepwise approach. - Methods - Men and women (N=569, age 18-75years) with any manifestation of CAD and depression scores ≥8 on the Hospital Anxiety and Depression Scale (HADS), will be randomized (allocation ratio 1:1) into the intervention or control group. Patients with severe heart failure, acutely life-threatening conditions, chronic inflammatory disease, severe depressive episodes or other severe mental illness are excluded. Both groups receive usual medical care. Patients in the intervention group receive three initial sessions of supportive individual psychotherapy. After re-evaluation of depression (weeks 4-8), patients with persisting symptoms receive an additional 25 sessions of combined psychodynamic and cognitive-behavioral group therapy. The control group receives one psychosocial counseling session. Primary efficacy variable is the change of depressive symptoms (HADS) from baseline to 18months. Secondary endpoints include cardiac events, remission of depressive disorder (SCID) and Type D pattern, health-related quality of life, cardiovascular risk profile, neuroendocrine and immunological activation, heart rate variability, and health care utilization, up to 24months of follow-up (ISRCTN: 76240576; NCT00705965). Funded by the German Research Foundation.